EXAMINING THE EFFECTS OF ENVIRONMENTAL COMPONENTS ON TOURISM DESTINATION COMPETITIVENESS: THE MODERATING IMPACT OF COMMUNITY SUPPORT - Chee-Hua, Chin,; May-Chiun, Lo,; Vikneswaran Nair,; Peter Songan, (Asian Academy of Management Journal, 2016)
Contemporarily, tourism sector is a highly competitive environment, which forces tourism players to provide better visitor services in order to stay competitive. In rural tourism, a growing niche in the tourism market, multiple components of environmental constructs play a crucial role in contributing to the sustainability and competitiveness of rural tourism destinations. Hence, this study examines the impact of environment components on development of rural tourism destination competitiveness from a local community perspective. In addition, community support was adopted as moderator variable to examine the relationship among the constructs. 299 respondents comprising of residents of rural tourism in Sarawak, Malaysia took part voluntarily in this study. Data analysis was performed using SPSS Version 21.0 and Smart PLS 2.0 (M3) to assess the developed model, based on path modelling and then bootstrapping. Interestingly, the findings revealed that four of the environmental constructs have had a significant positive impact on destination competitiveness from local communities' perspective.